Thermodynamic and transport properties of organic salts - Franzosini, Paolo; Sanesi, Manlio (IUPAC chemical data series ;, 1980)
Thermodynamic and Transport Properties of Organic Salts is concerned with the thermodynamic and transport properties of organic salts, namely, pure salts, mixtures, and solutions. The transport properties of pure molten salts and binary mixtures of molten salts with organic ions are given, along with the transport properties of organic salts in aqueous solutions. This book is divided into three sections and opens with a discussion on the statistical treatment and of computer simulation methods for molten salts as well as their results for pressure-volume-temperature (PVT) data. The PVT data fo.